Terrarium depicting the effects of colony collapse disorder - Ariñas, Jomari James U.; Feleo, Roberto; Sta. Ana, Mary Catherine (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Bees are dying around the world at a rapid rate. This phenomenon, called Colony Collapse Disorder, happens when worker bees fail to return to their hives, leaving the colony dysfunctional. There are many factors contributing to the demise of the bees, but the number one factor is pesticides. Without bees, many of our resources such as coconut, coffee, mangoes, beans as well as products such as dairy, cotton, paper, and of course, honey, to name a few, could vanish along with them. The absence of one resource may lead to the loss of another.

This thesis aims to depict the effects of Colony Collapse Disorder (CCD) on the human environment by creating a terrarium as a metaphor to human habitat, and create awareness about CCD. I created a post-apocalyptic scenario where miniature bee hives resemble a high density urban habitat. With the use of dead bees and terrarium, my work presents an allegory about human civilization when bees vanish from the face of the earth.
Thesis (Bachelor of Fine Arts in Painting)--University of the Philippines Diliman
Keywords: Terrarium; Colony collapse disorder; Environmental art